Optimalisasi SDM Remaja melalui Program Karakter dan Pengembangan Diri di Yayasan Tajaul Karomatu Desa Situ Gadung Kabupaten Tangerang - Ninik Anggraini; Angga Pratama; Sunanto Sunanto (Jurnal PKM Manajemen Bisnis, 2026)
Adolescent human resource development is essential for fostering positive character and personal growth. In Desa Situ Gadung, Tangerang Regency, students have limited access to structured programs that support character building and self-development. This community service activity aimed to optimize adolescent potential through character and self-development programs at Yayasan Tajaul Karomatu. The activity was conducted on October 25, 2025, and implemented by three lecturers from Universitas Pamulang. Participants were 23 grade 6 elementary school students. The implementation consisted of three stages: preparation, execution, and reporting. Methods included material presentation, practical exercises, group discussions, and question-and-answer sessions to promote engagement and understanding. The results indicated significant improvements in students’ understanding of character values, self-confidence, responsibility, and teamwork. Participants actively engaged in all activities and showed enthusiasm for applying the knowledge and skills in daily life. This program demonstrates the effectiveness of structured interventions in supporting holistic adolescent development and can serve as a model for similar initiatives aimed at strengthening youth potential in rural communities.